2021
DOI: 10.3390/toxics9090206
|View full text |Cite
|
Sign up to set email alerts
|

Early Low-Level Arsenic Exposure Impacts Post-Synaptic Hippocampal Function in Juvenile Mice

Abstract: Arsenic is a well-established carcinogen known to increase mortality, but its effects on the central nervous system are less well understood. Epidemiological studies suggest that early life exposure is associated with learning deficits and behavioral changes. Studies in arsenic-exposed rodents have begun to shed light on potential mechanistic underpinnings, including changes in synaptic transmission and plasticity. However, previous studies relied on extended exposure into adulthood, and little is known about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Acute hippocampal slices were prepared from 1-1.5 month-old mice of both sexes as described previously (Foley et al ., 2022; Foley et al, 2021b). After brief isoflurane anesthetization and decapitation, the brain was rapidly dissected and sectioned in an ice-cold high sucrose solution containing, in mM: 215 sucrose, 2.5 KCl, 26 NaHCO 3 , 1.6 NaH 2 PO 4 , 20 D-glucose, 1 CaCl 2 , 4 MgCl 2 , and 4 MgSO 4 .…”
Section: Star Methodsmentioning
confidence: 99%
“…Acute hippocampal slices were prepared from 1-1.5 month-old mice of both sexes as described previously (Foley et al ., 2022; Foley et al, 2021b). After brief isoflurane anesthetization and decapitation, the brain was rapidly dissected and sectioned in an ice-cold high sucrose solution containing, in mM: 215 sucrose, 2.5 KCl, 26 NaHCO 3 , 1.6 NaH 2 PO 4 , 20 D-glucose, 1 CaCl 2 , 4 MgCl 2 , and 4 MgSO 4 .…”
Section: Star Methodsmentioning
confidence: 99%
“…An equivalent number of events was randomly sampled from each I-2 WT cell, yielding 946 events. Acute hippocampal slices were prepared from 1-2-month old mice bred as previously described [30]. 400 μm thick slices were prepared after decapitation and rapid extraction of the brains into ice-cold artificial cerebrospinal fluid (ACSF).…”
Section: Electrophysiologymentioning
confidence: 99%
“…Studies have indicated that arsenic can contribute to nerve damage by inducing an inflammatory response in the hippocampus [ 44 ]. Additionally, arsenic has been found to impact hippocampal autophagy [ 45 ], mitochondrial function [ 46 ], and synaptic function [ 47 ]. As a result, this particular study aimed to investigate the pathological damage inflicted on hippocampal tissue due to arsenic exposure.…”
Section: Discussionmentioning
confidence: 99%